2004
DOI: 10.1111/j.1467-9353.2004.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Canada's Agricultural Trade in North America: Do National Borders Matter?

Abstract: Canada and the United States are each other's largest trading partner. Trade in agricultural goods has grown continuously since the signing of the Canada-United States Trade Agreement in 1989. The trade agreement removed most tariffs on traded agricultural goods. However, many nontariff barriers remain. We estimate the border effects for a select group of agricultural commodities and find that the quantity traded is less than would be predicted under free trade.T he Canada-United States Trade Agreement (1989) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…An analogous estimate for agricultural trade in the OECD does not exist. However Furtan and van Melle (2004), using a traditional gravity equation with a specification very close to column 1, found a border effect even stronger for Canada and US agricultural trade.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…An analogous estimate for agricultural trade in the OECD does not exist. However Furtan and van Melle (2004), using a traditional gravity equation with a specification very close to column 1, found a border effect even stronger for Canada and US agricultural trade.…”
Section: Resultsmentioning
confidence: 90%
“…Our focus on agricultural trade is motivated by the fact that while several papers analyzing national border effects in manufacturing sector (see Anderson and van Wincoop, 2004, for a survey) exist, the only paper published on this topic in agriculture is, to the best of our knowledge, that of Furtan and van Melle (2004) who estimate the border effects of the US, Canada and Mexico using a standard gravity model. Furthermore, agricultural products are characterized by high protection levels, complex tariff structures, low transportability and strong 'home bias' in preferences, all factors that induce large border effects.…”
Section: Introductionmentioning
confidence: 99%
“…It can be found that the intercepts differ quite a lot in three models: five intercepts in model (2) are all negative and the average of them tends to be greater in absolute value. While the intercept in average in model (3) for four borders is the least in value. But the intercept for every trading pair (200 pairs altogether) ranges from 4.032 to 17.019, indicating the great differences in determining the bilateral trade of each trading pair.…”
Section: B Variables Analysismentioning
confidence: 95%
“…Dascal et al [2] utilized pooled cross-sectional and time series data in a one-way fixed effects model. Furtan & van Melle [3] applied two traditional border effect gravity models and found the declining and asymmetric border effects for agricultural trade. Olper & Raimondi [4] included multilateral resistance in the model.…”
Section: Introductionmentioning
confidence: 99%
“…Some have paid attention to border effect of agricultural trade and made conclusion that border effect of agricultural trade is also significantly large among developed countries (Furtan & van Melle, 2004;Olper & Raimondi, 2005;Paiva, 2005). Besides, the border effect studies have been focusing more on advanced developed countries or regions than on developing countries.…”
Section: Introductionmentioning
confidence: 99%